2013
DOI: 10.1016/j.jebo.2013.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Self-serving altruism? The lure of unethical actions that benefit others

Abstract: In three experiments, we propose and find that individuals cheat more when others can benefit from their cheating and when the number of beneficiaries of wrongdoing increases. Our results indicate that people use moral flexibility to justify their self-interested actions when such actions benefit others in addition to the self. Namely, our findings suggest that when people’s dishonesty would benefit others, they are more likely to view dishonesty as morally acceptable and thus feel less guilty about benefiting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
235
2
13

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 321 publications
(261 citation statements)
references
References 27 publications
11
235
2
13
Order By: Relevance
“…Yet, when the benefits of lying do not clearly outweigh those of honesty in the eyes of the target, prosocial lies can harm trust and moral judgments, and communicating benevolent intent may do little to mitigate these negative effects (Lupoli, Levine, & Greenberg, 2017). Other work has focused on predictors of prosocial lying: Research reveals that people are more likely to lie when others stand to gain (Gino, Ayal, & Ariely, 2013;Gino & Pierce, 2009;Wiltermuth, 2011), and prosocial lying is observed even when there is a cost to the self (Erat & Gneezy, 2012). Thus far, however, no work has examined what is likely a critical antecedent of prosocial lying: emotion, and in particular, the emotion of compassion.…”
Section: Prosocial and Selfish Lyingmentioning
confidence: 99%
“…Yet, when the benefits of lying do not clearly outweigh those of honesty in the eyes of the target, prosocial lies can harm trust and moral judgments, and communicating benevolent intent may do little to mitigate these negative effects (Lupoli, Levine, & Greenberg, 2017). Other work has focused on predictors of prosocial lying: Research reveals that people are more likely to lie when others stand to gain (Gino, Ayal, & Ariely, 2013;Gino & Pierce, 2009;Wiltermuth, 2011), and prosocial lying is observed even when there is a cost to the self (Erat & Gneezy, 2012). Thus far, however, no work has examined what is likely a critical antecedent of prosocial lying: emotion, and in particular, the emotion of compassion.…”
Section: Prosocial and Selfish Lyingmentioning
confidence: 99%
“…On the other hand, a number of findings support the view that collaboration might have a liberating effect, freeing people to behave unethically. People lie more when it improves not only their own (14)(15)(16), but also others' outcomes (17)(18)(19)(20)(21); when their lies benefit a cause or another person they care about (22); and group-serving dishonesty is modulated by oxytocin, a social bonding hormone (23). The idea that collaboration will increase dishonest behavior is in line with the functionalist approach to morality, which prescribes that people treat morality in a flexible manner, judging the same act as illegitimate or immoral in some cases, but legitimate or even moral in other cases, e.g., when it profits one's group members (24,25).…”
mentioning
confidence: 99%
“…Indeed, in her testimony, the mother indicated that she deliberately took the risk of punishment to improve her children's chances in life (20). Such motivation to serve others, it stands to reason, is more powerful and makes it easier to generate justification for moral code breaking than a motivation to serve personal interests only (even when holding personal profit constant) (21)(22)(23)(24).…”
mentioning
confidence: 99%